The sex differences in the 10,000 m race strategy - Diego A. Borba; Pablo S. Rodrigues; Guilherme F. F. de Oliveira; João B. Ferreira Júnior (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: This study aimed to compare the running strategy between men and women in the 10,000 m race. Methods: Data from one-hundred and twenty-nine athletes who competed the 10,000 m final of the 2015, 2017 and 2019 world championship were grouped according to gender: 1) male group (n= 63; age= 25.9±4.4), and 2) female group (n= 66; age= 27.3±4.8). The running strategy was determined by assessing velocity over each kilometer. The velocity was calculated from the times available on the official website of the International Athletics Federation. Results: Men decreased running velocity after the first kilometer and kept the speed stable until km 9 and the kilometer 10 was greater when compared with 6-9 kilometer, while women increase running velocity until km 2 and kept the speed stable until km 9. The kilometer 10 velocity was greater when compared with 1-9 kilometer. (p< 0.001). In addition, women showed a greater average velocity variation when compared to men (p< 0.001). Conclusion: Our findings show a sex differences in the 10,000 m race strategy between world-class.